Psychodynamics of imagination failures: Reflections on the 20th anniversary of 9/11. Issue 4 (September 2021) - Fraher, Amy L
This article aims to advance the psychodynamic understanding of imagination failures by studying lessons learned in the US government's public inquiry into September 11th, 2001 (9/11). Analyzing the findings of The 9/11 Report, I theorize that two forms of macro-level hubris—America's "hubris of empire-building" and Al Qaeda's "hubris-nemesis complex"—amalgamated in a uniquely generative manner leading to events on 9/11. Previous studies of public inquiries often demonstrate that inquiry reports are monological story-telling performances used to create sense-making narratives that function hegemonically to impose a simplified version of reality to assign blame and depoliticize events in order to facilitate closure after shocking events. In contrast, findings here suggest that by constructing a critical narrative, The 9/11 Report may serve as a new type of public inquiry report that invites learning about the complex factors that underpin crisis. The article concludes by identifying fruitful areas of future research and ways to theorize further about the collective psychodynamics of macro-level hubris and the psychodynamic factors that hinder learning and contribute to imagination failures.